2018
DOI: 10.1038/s41576-018-0017-y
|View full text |Cite
|
Sign up to set email alerts
|

Towards a complete map of the human long non-coding RNA transcriptome

Abstract: Gene maps, or annotations, enable us to navigate the functional landscape of our genome. They are a resource upon which virtually all studies depend, from single-gene to genome-wide scales and from basic molecular biology to medical genetics. Yet present-day annotations suffer from trade-offs between quality and size, with serious but often unappreciated consequences for downstream studies. This is particularly true for long non-coding RNAs (lncRNAs), which are poorly characterized compared to protein-coding g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
419
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 513 publications
(422 citation statements)
references
References 158 publications
(232 reference statements)
2
419
0
1
Order By: Relevance
“…LncRNAs are diverse and abundant in each component of human life with the total number exceeding that of protein‐coding genes . The biological complexity of lncRNAs enables them to participate in various biological processes such as gene transcription, cell state coordination, and disease progression, while only a small proportion of lncRNAs are studied . As one of the novel lncRNAs, lnc‐THRIL is initially disclosed to regulate the expression of TNF‐α, which is a key mediator of inflammation and immune response by forming a complex with hnRNPL and then binding to the promoter region of TNF‐α, and it influences the expression of inflammatory cytokines such as IL‐1β, IL‐6, and IL‐8 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…LncRNAs are diverse and abundant in each component of human life with the total number exceeding that of protein‐coding genes . The biological complexity of lncRNAs enables them to participate in various biological processes such as gene transcription, cell state coordination, and disease progression, while only a small proportion of lncRNAs are studied . As one of the novel lncRNAs, lnc‐THRIL is initially disclosed to regulate the expression of TNF‐α, which is a key mediator of inflammation and immune response by forming a complex with hnRNPL and then binding to the promoter region of TNF‐α, and it influences the expression of inflammatory cytokines such as IL‐1β, IL‐6, and IL‐8 .…”
Section: Discussionmentioning
confidence: 99%
“…The biological complexity of lncRNAs enables them to participate in various biological processes such as gene transcription, cell state coordination, and disease progression, while only a small proportion of lncRNAs are studied. 6 As one of the novel lncRNAs, lnc-THRIL is initially disclosed to regulate the expression of TNF-α, which is a key mediator of inflammation and immune response by forming a complex with hnRNPL and then binding to the promoter region of TNF-α, and it influences the expression of inflammatory cytokines such as IL-1β, IL-6, and IL-8. 9,11 Additionally, lnc-THRIL is reported to influence inflammation-related cell injuries in inflammatory diseases, and cell injury, especially alveolar epithelial cells injury that is one of the main contributors for the development of ARDS in sepsis.…”
Section: Subgroup Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Recent advances in micro-array and sequencing technologies have revealed that large amounts of non-coding RNAs exist in cells. For example, in human cells, tens of thousands of long non-coding RNAs have been identified [1]. The functions of non-coding RNAs have been studied extensively, and relationships between mutations in non-coding RNAs and diseases have been investigated [2][3][4].…”
Section: Introductionmentioning
confidence: 99%